Influence of inclination angle of magnetic field on mixed convection of nanofluid flow over a backward facing step and entropy generation - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier, 2015)
In this paper, numerical study of laminar forced convection of nanofluid flow over a backward facing step for different inclination angles of magnetic field is performed. The bottom wall of the channel downstream of the step is isothermally heated and the other walls of the channel are assumed to be adiabatic. Finite element method was used to solve the governing equations. The influence of the Reynolds number (between 20 and 200), Hartmann number (between 0 and 50) and solid volume fraction of the nanoparticle (between 0 and 0.04) on the fluid flow and heat transfer are numerically investigated for different orientation angles of the magnetic field. It is observed the averaged heat transfer increases as the Reynolds number increases and this effect is more pronounced with higher values of inclination angle of the magnetic field. As the value of the Hartmann number decreases for horizontally aligned magnetic field and volume fraction of the nanoparticles increases averaged and local enhancement of heat transfer are observed. For the inclined and vertical magnetic field, suppression of the recirculation zone behind the step is observed as the value of Ha increases which results in heat transfer enhancement. The total entropy generation ratio increases with increasing values of Reynolds number, solid volume fraction of nanoparticles and decreasing values of Hartmann number for horizontally oriented magnetic field. (C) 2015 The Society of Powder Technology Japan. Published by Elsevier B.V. and The Society of Powder Technology Japan. All rights reserved.
Keywords: Backward facing step; MHD convection; Nanofluid; Finite element method